Free trade agreements and production sharing in Malaysian manufacturing industries - Choong, Pai Wei; Noor Aini Khalifah,; Abu Hassan Shaari Md Nor,; Mohd Adib Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Malaysia unilaterally reduced its tariff and expanded its bilateral manufactured exports in the 1990s. However, in the 2000s, Malaysia signed a growing number of free trade agreements (FTA) to lower its tariff among member countries. This study examines the impact of the growing number of FTAs on Malaysia’s bilateral manufactured exports at industry level in general and based on production sharing in particular over the period of 1990 to 2016 by three-year average. FTA-and-foreign input interaction term is embedded in the gravity equation model to examine the extent of FTAs in expanding production sharing-based bilateral manufactured exports. The empirical results of this study are based on dynamic panel system generalized method of moments (SYS-GMM) technique where FTA dummies are weakly exogenous. The findings show that the ASEAN Free Trade Area (AFTA) and bilateral trade agreements have significant impact on Malaysia’s non-resource-based exports and are associated with production sharing; while AFTA-plus-one shows no evidence of diverting Malaysian production sharing-based bilateral manufactured exports from its member countries. Moreover, FTA formation has no relation to the Malaysian resource-based exports. The proliferation of FTAs does not assure net export-enhancing effect on manufacturing activities among member countries, but is largely associated with international production sharing.